Pengaruh Kompres Hangat terhadap Penurunan Nyeri Dada pada Pasien Acute Coronary Syndrome (ACS) Diruang Icu Rumah Sakit Islam Ibnu Sina Bukittinggi Tahun 2025 - Violani Tri Suci; Reny Chaidir; Yossi Fitrina (LPPM Institut Pendidikan Nusantara Global, 2026)
Acute Coronary Syndrome (ACS) is a manifestation of ischemic heart disease characterized by chest pain resulting from myocardial ischemia. Chest pain management is commonly performed using pharmacological therapy; however, this approach may cause adverse effects, making non-pharmacological interventions such as warm compress therapy an important alternative. This study aimed to determine the effect of warm compresses on reducing chest pain in patients with ACS in the ICU of Ibnu Sina Islamic Hospital Bukittinggi in 2025. A quasi-experimental study with a one-group pretest-posttest design was conducted from April 29 to May 19, 2025. The sample consisted of 24 respondents selected using accidental sampling based on predetermined inclusion and exclusion criteria. Warm compresses at a temperature of 40–45°C were applied for 15 minutes once daily for two consecutive days. Pain intensity was assessed using the Visual Analog Scale (VAS) and analyzed using a paired t-test after the Shapiro-Wilk normality test. The findings showed that the mean chest pain score decreased from 5.75 before the intervention to 3.33 after the intervention. Statistical analysis revealed a t-value of -20.287 with a p-value of 0.000 (p < 0.05), indicating a statistically significant difference in pain scores before and after the intervention. Warm compress therapy was proven to effectively reduce chest pain intensity in patients with ACS treated in the ICU. This intervention is recommended as a safe and effective non-pharmacological therapy that can be incorporated into nursing practice to improve patient comfort.